Transformasi Digital untuk Meningkatkan Daya Saing UMKM dan Kemandirian Ekonomi Masyarakat Desa Sawarna - Siti Setiawati; Muhamad Rajwa Athoriq; Arief Surya Awangga; Alfredo Alusiyus Octavianus; Erikson Imanuel; Fitriani Novita Putri Nugroho; Indah Leandra Tiara; Muhamad Ihsan; Muhammad Fachmi As Salam; Muhammad Zain Al’farysi; Virendra Martiza Putra; Luthfi Restu Adji (Journal Of Computer Science Contributions (JUCOSCO), 2025)
The rapid development of digital technology demands both micro, small, and medium enterprises (MSMEs) and young generations to possess adequate digital competencies in order to remain competitive. However, observations in Sawarna Village indicate that many MSME actors have not been able to optimize digital marketing strategies, particularly the use of affiliate marketing features on TikTok Shop and Shopee. Similarly, students at SMAN 2 Bayah still experience limitations in mastering Microsoft Excel, a fundamental skill required in various professional fields. This community service program aims to enhance the digital capacity of both partners through an Affiliate Marketing Workshop for MSMEs and an Excel for the Workplace Training Program for high school students. The implementation consisted of preparation, execution, and evaluation stages using interactive lectures, demonstrations, and hands-on learning. The results show a significant improvement in MSME participants’ understanding of affiliate marketing concepts, activation of affiliate features, content creation, and digital promotion strategies. Furthermore, Excel training effectively improved students’ abilities in using basic to intermediate functions, processing data, and creating tables and charts. Overall, the program successfully strengthened digital literacy among MSMEs and improved students’ job readiness skills, contributing positively to the community in Sawarna Village.